Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3389/fphy.2020.575732
|View full text |Cite
|
Sign up to set email alerts
|

Optical Force Measurements Illuminate Dynamics of Escherichia coli in Viscous Media

Abstract: Escherichia coli and many other bacteria swim through media with the use of flagella, which are deformable helical propellers. When the viscosity of media is increased, a peculiar phenomenon can be observed in which the organism's motility appears to improve. This improvement in the cell's swimming speed has previously been explained by modified versions of resistive force theory (RFT) which accounts for the interaction between flagella and molecules associated with the viscosity increase. Using optical tweeze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…(1). Although models predict a viscosity dependence, recent studies have found that F is independent of viscosity ( Armstrong et al, 2020 ). This equation of motion yields a terminal velocity of…”
Section: Introductionmentioning
confidence: 99%
“…(1). Although models predict a viscosity dependence, recent studies have found that F is independent of viscosity ( Armstrong et al, 2020 ). This equation of motion yields a terminal velocity of…”
Section: Introductionmentioning
confidence: 99%
“…We show, in an experiment, that single descents can be used to calibrate the optical trap where large trap strengths restrict the performance of equilibrium measurements as they are in a regime where the signal is too close to the detection noise floor. This type of calibration is ideal for multiple and dynamic optical traps to rapidly determine the swimming forces of optically driven micromachines, active matter, and cells on the two micron size scale [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%